2008
DOI: 10.1007/s11064-008-9672-2
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity Neurotensin Receptor is Involved in Phosphoinositide Turnover Increase by Inhibition of Sodium Pump in Neonatal Rat Brain

Abstract: Phosphoinositide (PI) metabolism is enhanced in neonatal brain by activation of neurotransmitter receptors and by inhibition of the sodium pump with ouabain or endogenous inhibitor termed endobain E. Peptide neurotensin inhibits synaptosomal membrane Na(+), K(+)-ATPase activity, an effect blocked by SR 48692, a selective antagonist for high-affinity neurotensin receptor (NTS1). The purpose of this study was to evaluate potential participation of NTS1 receptor on PI hydrolysis enhancement by sodium pump inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Results showed that antagonist SR 48692 blocks the inhibitory effects of ouabain on sodium pump modulating phosphoinositide hydrolysis. This result suggests that high-affinity neurotensin receptors are involved, at least partially, in the process [36]. These findings may receive a new interpretation in the ligth of present results.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Results showed that antagonist SR 48692 blocks the inhibitory effects of ouabain on sodium pump modulating phosphoinositide hydrolysis. This result suggests that high-affinity neurotensin receptors are involved, at least partially, in the process [36]. These findings may receive a new interpretation in the ligth of present results.…”
Section: Discussionsupporting
confidence: 76%
“…Herein we showed an interference between SR 48692 and ouabain at the Na + , K + -ATPase ouabain binding site. Therefore, it seems reasonable that the phosphoinositide hydrolysis increase by Na + , K + -ATPase inhibitors is prevented by in vitro addition of SR 48692 [36].…”
Section: Discussionmentioning
confidence: 99%
“…For example, neurotensin inhibits Na + /K + -ATPase activity of synaptosomal membranes from rat cerebral cortex (Lopez Ordieres and Rodriguez de Lores Arnaiz 2000). Neurotensin exerts these effects through activation of NTS1 receptors that results in PI hydrolysis (Pereyra-Alfonso et al 2008). In contrast, sub-µM angiotensin-(1-7) activates Na + /K + -ATPase from rat cerebral cortex synaptosomal membranes (Lopez Ordieres et al 1998).…”
Section: Na+/k+-pump and Regulation Of Neurotransmitter Receptors By mentioning
confidence: 99%